Dual Energy Management and an Energy-Saving Model for the Internet of Things Using Solar Energy Harvesting - Nasser S. Albalawi; Jerzy W. Rozenblit; Pratik Satam; Janet Meiling Roveda (Energies, 2025)
The Internet of Things (IoT) is a fast-growing internet technology and has been incorporated into a wide range of fields. The optimal design of IoT systems has several challenges. The energy consumption of the devices is one of these IoT challenges, particularly for open-air IoT applications. The major energy consumption takes place due to inefficient routing, which can be addressed by the energy-efficient clustering method. In addition, the energy-harvesting method can also play a significant role in increasing the overall lifetime of the network. Therefore, in the proposed work, a novel energy-efficient dual energy management and saving model is proposed to manage the energy consumption of IoT networks. This model uniquely integrates energy-efficient clustering with solar energy harvesting (SEH) to address IoT energy challenges. The dual elbow method is utilized for efficient clustering to ensure guaranteed quality of service (QoS), while SEH enhances energy sustainability. The proposed method is implemented for high-density sensor network applications. Simulation results demonstrate a 25% reduction in overall energy consumption and a 20% increase in network lifetime compared to existing methods. Our model will be able to manage energy consumption and increase the IoT network’s overall lifetime by optimizing IoT devices’ energy consumption.